Determinan Ekspor CPO Indonesia - Ratih Rosita; Haryadi Haryadi; Amril Amril (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2014)
Palm oil is one of the products that are important to the economy of Indonesia. This study aims to analyze the performance of Indonesia's CPO exports and to look for the influence of the independent variables such as production volume CPO, CPO consumption and the value of the rupiah against the U.S. dollar. The authors of this study tested using the Method of Error Correction Model. The time interval used is from 1998 to 2011 with the data quarter. The findings suggest that Indonesia's CPO production volume variables exert a positive and significant impact on the number of Indonesian CPO exports in both the short and long term, then the variable volume Indonesia CPO consumption in the short and long term is also a significant effect on the number of Indonesian CPO exports but negatively related, this is due to the domestic CPO consumption greater that the capacity to export will be reduced. Variables of the Rupiah against the U.S. dollar also affects Indonesia's CPO exports significantly and negatively related to both the short and long term and conditions of the depreciation of the rupiah exchange rate is not enough to effectively be driving exports. Estimates show that the close relationship between external demand caused exports to Indonesia's export performance vulnerable to external shocks. Side factors are also a determinant of export performance. Keywords: palm oil, CPO consumption, Error Correction Model